Kinerja Koperasi Kredit Kubu Gunung Tegaljaya Desa Dalung Kecamatan Kuta Utara Kabupaten Badung (Pendekatan Balanced Scorecard) - DEWI, MADE PUTRI KRISNA; ANTARA, MADE; USTRIYANA, I NYOMAN GEDE (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.4, No.3, Juli 2015, 2016)
Abstract Performance Koperasi Kredit Kubu Gunung Tegaljaya Dalung Village, Kuta Utara Sub-district Badung Regency (Approach Balanced Scorecard) Cooperative is the only entity which compatible with national economic system. Cooperative has position as “soko guru” of national economic and as a part which cannot be separated from national economic system. The purpose of research is to know how the performance of Kredit Kubu Gunung Tegaljaya Cooperative based on balance scorecard that observed with financial perspective, consumen perspective, internal business process perspective, research and development perspective during 2009 until 2013. The type of data collected is quantitative and qualitative data. Data collection methods used were interviews and questionnaires. Data analysis method used is the balanced scorecard method and descriptive qualitative. According to financial perspective analysis of liquidity ratio represents a the worst performance, solvability ratio represents bad performance, and profitability ratio represents worse performance. Whereas, according to consumen perspective shows the increasing amount of member is good, and the satisfication of member shows a satisfied attitude. According to internal business process perspective represent an efficient process. From research and development ratio shows that productivity and retention of employee is good, and based on the satisfication of employee shows a satisfied attitude. The conclusion based on four perspectives of balance scorecard represent that the performance is good enough. The suggestion for Kredit Kubu Gunung Tegaljaya Cooperative is should be able to increase the capital. Keywords : cooperative, balance scorecard , performance, credit